Behavioral Patterns and Spatial-Activity Dynamics of Urban Park Users : (A Behaviour Mapping Study of Prestasi Park, Surabaya) - Rosanti, Natasya Evita Putri; Setyono, Deni Agus; Surjono; Maulidi, Chairul (RUAS, 2026)
This study aims to analyze user behaviour in an urban park, where activities vary across different zones and time periods within the same area. Observations were conducted across eight time sessions, both on weekdays and weekends. A behavior mapping method that used place-centered mapping was used, and 1,899 users were recorded. The findings indicate that user behavior varies significantly across time and space. Most people visit in the morning and afternoon, but fewer people visit at noon due to thermal discomfort. Visits on the weekend are more common and have a higher percentage of active participation. In terms of space, Zones A and B are where people are actively involved in social and play activities, while Zones C and D are mostly where people are passively enjoying recreation and meals. The novelty of this study lies in the integration of temporal and spatial analysis. It demonstrates that behavioral variation occurs at a micro-scale across zones within a single park and changes over time. This study enhances user-oriented urban park planning by offering empirical evidence on the combined effects of spatial configuration and temporal rhythms on user behavior. The results show how important it is to design urban parks that can handle a wide range of activities, temporal dynamics, and spatial functions in order to enhance usage and inclusivity.